Numerical analysis of spontaneous mid-infrared light emission from terbium ion doped multimode chalcogenide fibers - Sujecki, Slawomir; Sojka, Lukasz; Pawlik, Elzbieta; Anders, Krzysztof; Piramidowicz, Ryszard; Tang, Zhuoqi; Furniss, David; Barney, Emma; Benson, Trevor; Seddon, Angela (Elsevier, 2018)
In this contribution we use a numerical model to study the photoluminescence emitted by Tb3+ doped chalcogenide-selenide glass fibers pumped by laser light at approximately 3 µm. The model consists of the set of ordinary differential equations (ODEs), which describe the spatial evolution of the pump laser and MIR photoluminescence light within the fiber. The ODEs are coupled with the rate equations that describe the energy level populations. A self-consistent solution of the equation system yields the pump light, MIR photoluminescence and level population distribution within the fiber. Using the developed model we numerically calculate results and discuss the dependence of the output photoluminescence MIR power on the fiber optical loss, fiber length and pump wavelength.